A novel selective mitochondrial-targeted curcumin analog with remarkable cytotoxicity in glioma cells - Shi, Lei; Gao, Li-li; Cai, Shi-zhong; Xiong, Qian-wei; Ma, Zhou-rui (European journal of medicinal chemistry, 2021)
Naturally occurring polyphenol curcumin (4) or demethoxycurcumin (5) and their synthetic derivatives display promising anticancer activities. However, their further development is limited by low bioavailability and poor selectivity. Thus, a mitochondria-targeted compound 14 (DMC-TPP) was prepared in the present study by conjugating a triphenylphosphine moiety to the phenolic hydroxyl group of demethoxycurcumin to enhance its bioavailability and treatment efficacy. The in vitro biological experiments of DMC-TPP showed that it not only displayed higher cytotoxicity as compared with its parent compound 5, but also exhibited superior mitochondria accumulation ability. Glioma cells were more sensitive to DMC-TPP, which inhibited the proliferation of U251 cells with an IC50 of 0.42 μM. The mechanism studies showed that DMC-TPP triggers mitochondria-dependent apoptosis, caused by caspase activation, production of reactive oxygen species (ROS) and decrease of mitochondrial membrane potential (MMP). In addition, DMC-TPP efficiently inhibited cellular thioredoxin reductase, which contributed to its cytotoxicity. Significantly, DMC-TPP delayed tumor progression in a mouse xenograft model of human glioma cancer. Taken together, the potent in vitro and in vivo antitumor activity of DMC-TPP warrant further comprehensive evaluation as a novel anti-glioma agent. [Display omitted] •A novel selective mitochondria-targeted curcumin analog DMC-TPP was prepared.•DMC-TPP exhibited potent cytotoxic effects in glioma cells.•DMC-TPP efficiently inhibited cellular thioredoxin reductase.•DMC-TPP delayed tumor progression in a mouse xenograft model of human glioma cancer.